Rice information extraction using multi-polarization airborne synthetic aperture radar data - LI Kun; SHAO Yun; ZHANG Feng-li (浙江大学学报. 农业与生命科学版, 2011)
Using multi-polarization (HH/HV/VH/VV) airborne synthetic aperture radar (SAR) data, polarimetric responses of rice and typical features and their differences were analyzed, then rice identification method based on its characteristics of polarimetric response was established. The results showed that backscattering coefficients of rice in different polarizations were of great difference, and the difference between horizontal polarization (HH) and vertical polarization (VV) of rice was significantly higher than other surface features. Based on the characteristic, rice information was extracted using the ratio of horizontal and vertical polarizations［〈HH〉/〈VV〉］, and good results were achieved. Rice identification accuracy was over 90%. The image enhanced rice information was classified. Classification result showed that rice of different growth stages can be distinguished to some extent.